Effects of selective NMDA and non-NMDA blockade in the nucleus accumbens on the plus-maze test - Martínez, Gabriel (2002)
Effect of blocking N-methyl-D-aspartic acid (NMDA) and non-NMDA-glutamatergic receptors on performance in the plus-maze was studied in male rats bilaterally cannulated into the nucleus accumbens (Acc). Rats were divided into seven groups that received either 1 μl injections of saline, (±)2-amino-7-phosphonoheptanoic acid (AP-7, 0.2, 0.5, or 1 μg) or 2,3 dioxo-6-nitro-1,2,3,4,tetrahydrobenzo-(f)quinoxaline-7-sulphonamide disodium (NBQX, 0.2, 0.5, or 1 μg) 15 min before testing. Time spent in open arm, time per entry, end arrivals, open, closed, and total arm entries, relationship between open-, closed-, and total arm entries, rearing, face-, head-, and body grooming, and number of fecal boli were recorded. Time spent in the open arm increased under AP-7 (0.5 and 1 μg; P<.01) and NBQX (1 μg; P<.05) treatment, whereas time per entry was increased only with AP-7 (1 μg; P<.05). Open arm entries were increased by the intermediate doses of AP-7 (0.5 μg; P<.01) and NBQX (0.5 μg; P<.05); end arrivals were increased by the intermediate dose of AP-7 (0.5 μg/1 μl, P<.05). The frequency of rearing, grooming, and closed arm entries was not affected by the treatment. We conclude that NMDA and non-NMDA-glutamatergic blockade in the Acc lead to a behavioral disinhibition of cortical influences with the median doses, but that at higher doses the blockers have an anxiolytic-like effect.